2020
DOI: 10.1097/md.0000000000023477
|View full text |Cite
|
Sign up to set email alerts
|

CD74, a novel predictor for bronchopulmonary dysplasia in preterm infants

Abstract: Bronchopulmonary dysplasia (BPD) remains a major complication and accounts for high morbidity and mortality of preterm infants. The present study aimed to identify the key genes in the development of BPD and to provide some new insights into the pathogenesis of BPD. The GSE108754 dataset was downloaded from Gene Expression Omnibus database containing 5 samples of BPD patients and 6 of non-BPD infants. The differentially expressed genes (DEGs) between BPD and non-BPD patients were identified by R software. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Two core gene programs (GM2 and GM3) characterized “Phagocytosis-Th2”, which included gene networks involved in leukocyte migration (5.3%, FDR = 9.15E-05), osteoclast differentiation (4.5%, FDR = 0.006), receptor-mediated endocytosis (5.7%, FDR = 7.03E-04, COLEC12, MSR1, CD163), and antigen processing and presentation via MHC class II (6%, p = 1.42E-13, HLA-DMA ( Gao et al, 2020 ), HLA-DRB5, HLA-DMB, HLA-DRB4, HLA-DPB1, HLA-DRA, HLA-DRB3, HLA-DOA, HLA-DQA2 ( Lasky-Su et al, 2012 ), HLA-DRB1, HLA-DPA1). The clinical characteristics showed that the eosinophils (mean: 4, p = 0.0009) were abnormally increased in blood.…”
Section: Resultsmentioning
confidence: 99%
“…Two core gene programs (GM2 and GM3) characterized “Phagocytosis-Th2”, which included gene networks involved in leukocyte migration (5.3%, FDR = 9.15E-05), osteoclast differentiation (4.5%, FDR = 0.006), receptor-mediated endocytosis (5.7%, FDR = 7.03E-04, COLEC12, MSR1, CD163), and antigen processing and presentation via MHC class II (6%, p = 1.42E-13, HLA-DMA ( Gao et al, 2020 ), HLA-DRB5, HLA-DMB, HLA-DRB4, HLA-DPB1, HLA-DRA, HLA-DRB3, HLA-DOA, HLA-DQA2 ( Lasky-Su et al, 2012 ), HLA-DRB1, HLA-DPA1). The clinical characteristics showed that the eosinophils (mean: 4, p = 0.0009) were abnormally increased in blood.…”
Section: Resultsmentioning
confidence: 99%
“…Low birth weight and preterm birth may also be risk factors for BPD and asthma [ 33 ]. At the molecular level, Gao et al reported that functional enrichments and pathways showed that the different expression of genes in BPD and non-BPD infants was mainly enriched in asthma [ 34 ]. Surfactant protein D, a pattern-recognition molecule belonging to the collectin family, was reported to correlate with the development of respiratory diseases, including allergic asthma and BPD [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, HLA-DOB was observed to be one of the 13 key differentially expressed genes in preterm infants who developed bronchopulmonary dysplasia (BPD) and expression was increased in infants with BPD. 33 Due to hypomethylation of HLA-DOB CpGs with COVID-19 infection in pregnancy, expression of HLA-DOB is likely to be increased in preterm infants and could potentially increase the risk of BPD. The top hypermethylated genes included XYLB (Xylulose kinase), CLDN6 (Claudin-6), UBTF (Upstream binding transcription factor), LPCAT2 (Lysophosphatidylcholine acyltransferase 2), STRN4 (Striatin 4), and HLA-DPB1 (Major histocompatibility complex, class II, DP beta 1).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, HLA-DOB was observed to be one of the 13 key differentially expressed genes in preterm infants who developed bronchopulmonary dysplasia (BPD) and expression was increased in infants with BPD. 33 Due to hypomethylation of HLA-DOB CpGs with COVID-19 infection in pregnancy, expression of HLA-DOB is likely to be increased in preterm infants and could potentially increase the risk of BPD.…”
Section: Discussionmentioning
confidence: 99%